How do we process prices? Electrophysiological evidence of componential analysis. - Ojedo, Fernando; Macizo, Pedro (British Journal of Psychology, 2020)
The aim of this study was to evaluate if the processing of prices (e.g., 8 euro) involves separate analysis of the digit (8) and the monetary category (euro). Event‐related potentials (ERPs) were recorded when participants performed a price comparison task in which a pair of prices was presented and they selected the one with higher monetary value. There were compatible comparisons where the digit and the monetary category of one price were higher than those of the other price (e.g., 7 euro – 4 cent, 7 > 4 and euro > cent), and incompatible comparisons where the number of one price was larger but the monetary category smaller than those of the other price (e.g., 4 euro – 7 cent, 4 < 7 but euro > cent). Compatibility effect modulated ERPs in the 350–450 ms time window, with more negative amplitudes in incompatible trials relative to compatible trials. This pattern of results suggests that prices were processed in a componential manner, challenging the evidences of the holistic model. The results of this study agree with the general model framework for multi‐symbol number comparison: The constituents of a multi‐symbol magnitude are processed and compared to each other separately in a componential manner.